The Jewish Concept of the Covenant According to Max Weber - Chmielewska, Lucyna (W kręgu wyobrażeń zbiorowych. Polityka, władza, społeczeństwo, 2019)
In Max Weber’s interpretation, the covenant was a political instrument of the Israelites. In Weber’s view, the original goal of the Sinai covenant was the political goal – strengthening the defense force of scattered Israeli tribes, and within the tribes it gave the durability of socio-economic relations between social groups, mainly between shepherds of small herds and a farmers or a city military patriciate owning land. The covenant had a defensive character with regard to the tribal union and socio-political character in terms of intertribal relations. Israel was developing and gaining its specific character as a cult and military union based on free shepherds and farmers, uniting during the wars against enemies. In the later age of prophets, the covenant became a catalyst for the process of rationalizing and ethicizing the Jewish religion. This process was, therefore, a consequence of the development of the political consciousness of the Israelites, expressed in the form of the covenant with Yahweh.